ผลการจัดการเรียนรู้เพศศึกษาโดยใช้โมเดลเลิฟเพื่อสร้างเสริมความเป็นมนุษย์ ที่สมบูรณ์ของนักเรียนระดับชั้นมัธยมศึกษาตอนต้น - ธัญญศิริ นวรัตน์ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2018)
บทคัดย่อ การวิจัยกึ่งทดลองนี้ มีวัตถุประสงค์เพื่อศึกษาผลการจัดการเรียนรู้เพศศึกษาโดยใช้โมเดลเลิฟที่มีต่อการสร้างเสริมความเป็นมนุษย์ที่สมบูรณ์ ผลสัมฤทธิ์ทางการเรียน และความพึงพอใจต่อการจัดการเรียนรู้เพศศึกษาโดยใช้โมเดลเลิฟของนักเรียนมัธยมศึกษาตอนต้น กลุ่มตัวอย่างเลือกแบบเจาะจง เป็นนักเรียนระดับชั้นมัธยมศึกษาปีที่ 2 โรงเรียนสาธิตจุฬาลงกรณ์มหาวิทยาลัย ฝ่ายมัธยม จำนวน 60 คน เครื่องมือวิจัยประกอบด้วย 1) แผนการจัดการเรียนรู้เพศศึกษาโดยใช้โมเดลเลิฟ 2) แบบวัดความเป็นมนุษย์ที่สมบูรณ์ 3) แบบวัดผลสัมฤทธิ์ทางการเรียน และ 4) แบบวัดความพึงพอใจต่อกิจกรรมการจัดการเรียนรู้โดยใช้โมเดลเลิฟ ซึ่งผ่านการประเมินคุณภาพด้วยความตรงเชิงเนื้อหา มีค่ามากกว่า 0.5 และมีค่าความเที่ยงรายฉบับ ดังนี้ 1) แบบวัดความเป็นมนุษย์ที่สมบูรณ์ (ความดี 0.82 ความจริง 0.8 และความรู้ปฏิบัติ 0.8) และ 2) แบบวัดผลสัมฤทธิ์ทางการเรียน (ความรู้ 0.83 ทัศนคติ 0.81 และการปฏิบัติ 0.82) วิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าที และความแปรปรวนพหุคูณ ตลอดจนการวิเคราะห์ข้อมูลเชิงคุณภาพ ผลการวิจัยพบว่า 1) หลังเรียนกลุ่มทดลองมีพัฒนาการที่ดีขึ้นและดีกว่ากลุ่มควบคุมในด้านความเป็นมนุษย์ที่สมบูรณ์ อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2) หลังเรียนกลุ่มทดลองมีผลสัมฤทธิ์ทางการเรียนสูงกว่าก่อนเรียน และมีคะแนนเฉลี่ยสูงกว่ากลุ่มควบคุมด้านความรู้ และทัศนคติ อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 3) ความพึงพอใจของนักเรียนต่อการจัดการเรียนรู้เพศศึกษาโดยใช้โมเดลเลิฟอยู่ในระดับมาก คำสำคัญ : โมเดลเลิฟ, เพศศึกษา, ความเป็นมนุษย์ที่สมบูรณ์, นักเรียนระดับชั้นมัธยมศึกษาตอนต้น ABSTRACT This quasi-experiment research was designed to study sex education management using LOVE Model for comprehensive humanization learning achievement and determine student satisfaction regarding such instructional management among lower secondary school students. The sample was taken by using purposive sampling. There were sixty eighth grade students of Chulalongkorn University Demonstration Secondary School. The instruments in this study included: 1) sex education plans using LOVE Model for comprehensive humanization, 2) comprehensive humanization assessment, 3) learning achievement assessment, and 4) student satisfaction assessment. These instruments were also tested for content validity, which exceeded 0.5, and each assessment had reliability scores as follows: 1) the comprehensive humanization assessment had a score of goodness at 0.82, truth at 0.8, and knowledge for practices at 0.8; and 2) the learning achievement assessment had a score of knowledge at 0.83, attitude at 0.81, and practice at 0.82. The data were analyzed using mean, standard deviation, t-test, and MANOVA. In addition, content analysis.The study found that 1) following the experiment, the experiment group performed better and scored higher than the control group in comprehensive humanization, with statistical significance at .05 level; and 2) following the experiment, the experiment group performed better than before experiment and scored higher than the control group on student learning achievement both in knowledge and attitude, with statistical significance at .05 level. Furthermore, the former scored higher than the latter in sex education practice, but without statistical significance at .05 level and 3) the student satisfactions regarding sex education management using LOVE Model was also excellent. Keywords : LOVE model, sex education, comprehensive humanization, secondary school students